PENGENALAN HIDROPONIK: SOLUSI MENGURANGI KECANDUAN GADGET PADA ANAK - Sari, Nove Kurniati; Banyuriatiga, Banyuriatiga (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The main problem currently faced is the increasing use of digital devices, especially among children under the age of 10, which can cause addiction and have a negative impact on children's development. The purpose of this Community Service activity is to increase the understanding and knowledge of parents who have children under the age of 10 regarding the hydroponic garden system and its potential to reduce gadget addiction in children. This activity uses interactive lecture and discussion methods to present materials related to the basic concepts, benefits, and techniques for implementing hydroponic farming. The discussion session gives participants the opportunity to ask questions and express their opinions so that their understanding of hydroponics deepens. The discussion includes the potential of hydroponic farming in developing children's creativity, environmental awareness, social interaction, and sense of responsibility. Hydroponic gardening activities are expected to divert children's attention from gadgets to productive and educational activities. In conclusion, hydroponics has great potential to reduce children's gadget addiction. Children's involvement in hydroponic gardening activities can develop healthier and more productive skills and habits, effectively diverting their attention from gadget screens.